Translation, transcultural adaptation and validation of the Nordic questionnaire for the evaluation of low back pain in Brazilian adolescents - Oliveira, Raphael Gonçalves de; Pires-Oliveira, Deise Aparecida de Almeida; Oliveira, Laís Campos de; Remonte, Anne Karoline; Garcia, Sandy Caroline; Araújo, Camila Costa de; Jassi, Fabrício José; Ramos, Wagner Luiz; Venâncio, Patrícia Espíndola Mota; Júnior, Jairo Teixeira; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: Low back pain has been configured as a public health problem capable of compromising functional capacity, even in adolescents, however, there are no validated instruments for Brazilian adolescents. Objective: Validate the psychometric properties of the Nordic questionnaire for the evaluation of low back pain in Brazilian adolescents. Methods: The sample consisted of 150 adolescents (84 female), aged between 15 and 19 years. The Nordic questionnaire for the evaluation of low back pain in adolescents, was translated and culturally adapted into Portuguese (Brazil). A committee of experts followed the entire validation process. The questionnaire was administered in two moments, with a 14-day interval. Statistical analysis involved Kappa index. Results: After the slight modifications in the translation process, the expert committee considered that the Brazilian Portuguese version of the questionnaire presented semantic, idiomatic, cultural and conceptual equivalence. The results showed that, among the 15 items considered in the eight questions of the questionnaire, 66.6% presented substantial agreement (kappa between 0.61-0.80). The other items presented almost perfect agreement (kappa > 0.80). Conclusion: The Nordic questionnaire for the evaluation of low back pain in adolescents, after being translated and culturally adapted into the Portuguese (Brazil) language, showed adequate psychometric properties, with high reproducibility in all items, demonstrating that it can be used safely to evaluate the low back pain in Brazilian adolescents.